1996
DOI: 10.1021/ef9501410
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Asphaltenes during Artificial Maturation:  A Record of the Chemical Processes

Abstract: Type II kerogens have been artificially matured by confined and hydrous pyrolysis. The asphaltenes recovered from the experiments were characterized by FT-IR, synchronous UV fluorescence, Py-GC-MS, and elemental analysis. The results show that important modifications related to the physicochemical maturation conditions affect the asphaltenes:  (i) The asphaltenes yields are modified by temperature, pressure and by the presence of water. (ii) A progressive defunctionalization and increased aromatic content duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 47 publications
5
31
0
1
Order By: Relevance
“…Behar et al (2008b) proposed a kinetic scheme where kerogen initially decomposes into a very viscous, NSO-rich liquid which is further decomposed into more soluble non-hydrocarbon compounds and finally, cracked into hydrocarbons. The occurrence of a heavy, intermediate bitumen phase was also proposed by Michels et al (1996) and Lewan (1997). In this study, RockEval data for unextracted and extracted samples confirm the presence of a substantial amount of a non-volatile bitumen phase within the low maturity Posidonia shale (cf.…”
Section: Organic Matter Maturation Migration and Trappingsupporting
confidence: 79%
“…Behar et al (2008b) proposed a kinetic scheme where kerogen initially decomposes into a very viscous, NSO-rich liquid which is further decomposed into more soluble non-hydrocarbon compounds and finally, cracked into hydrocarbons. The occurrence of a heavy, intermediate bitumen phase was also proposed by Michels et al (1996) and Lewan (1997). In this study, RockEval data for unextracted and extracted samples confirm the presence of a substantial amount of a non-volatile bitumen phase within the low maturity Posidonia shale (cf.…”
Section: Organic Matter Maturation Migration and Trappingsupporting
confidence: 79%
“…Peters et al [10], Rohrback et al [11], and Huang [12], among others, have simulated maturation processes through experimental maturation studies in the laboratory. Monthioux et al [13], Landais and Monthioux [14], Landais et al [15,16], Benkhedda et al [17], Gérard et al [18], Mansuy and Landais [19], Mansuy et al [20], Michels et al [21][22][23], Landais and Gérard [24], and Han et al [25] have also shown that this maturation technique is able to reproduce the thermal transformation of kerogen and the generation of oil and gas according to natural evolution trends.…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, the fluorescence efficiency increases significantly with the increase of aromatic rings. In consideration of the ''red shift'' effect caused by alkylation and heteroatom, the numbers of aromatic rings of the compounds were summarized as follows: 270-300 nm for single-ringed aromatics, 300-340 nm for double-ringed aromatics, 340-400 nm for three aromatic rings, 400-425 nm for four aromatic rings, lager than 425 nm for five-and above five-ringed aromatics (Michels et al 1996).…”
Section: Listed the Rdb Of [M ? H]mentioning
confidence: 99%